The aboveground and belowground growth characteristics of juvenile conifers in the southwestern United States. Issue 11 (25th November 2021) - Pirtel, N. L.; Hubbard, R. M.; Bradford, J. B.; Kolb, T. E.; Litvak, M. E.; Abella, S. R.; Porter, S. L.; Petrie, M. D.
Abstract: Juvenile tree survival will play an important role in the persistence of coniferous forests and woodlands in the southwestern United States (SWUS). Vulnerability to climatic and environmental stress declines as trees grow, such that larger, more deeply rooted juveniles are less likely to experience mortality. It is unclear how juvenile conifers partition the aboveground and belowground components of early growth, if growth differs between species and ecosystem types, and what environmental factors influence juvenile carbon allocation above‐ or belowground. We developed a novel data set for four juvenile conifer groups (junipers, piñon pines, ponderosa pines, firs; 1121 juveniles sampled, 221 destructively) in three height classes (<150 mm, 150–300 mm, and 300+ mm), across 25 SWUS sites. We compared growth characteristics across groups and height classes and related differences to climatic and environmental factors. As tree height increased from <150 mm to 300+ mm, belowground growth increased, root:shoot ratio declined, and specific leaf area declined for all conifers except firs. Maximum rooting depth was shallower than previous estimates (<˜400 mm). Lower elevation juveniles were frequently located in sheltered microsites that provided high shading, whereas mid‐ and higher elevation juveniles were frequently unsheltered. Across all forest and woodland sites, herbaceous cover was positively correlated with aboveground growth. At study locations comprised of multiple sites, differences in aboveground growth were best explained by ecosystem type (piñon pine‐juniper woodland, ponderosa pine forest, mixed‐conifer forest) and local environmental variation. Our results indicate generally more belowground early growth and more aboveground later growth, but specific allocation patterns varied among ecosystem (greater proportional shoot growth at lower and mid‐elevations compared with higher elevations). Juvenile conifers had similar magnitudes of proportional growth across conifer groups, displaying limited capacity to acclimate growth to differences in climate that control ecosystem type. If juvenile conifers also do not acclimate physiologically to their environment, our findings suggest that local environmental variation will play a primary role in regulating forest and woodland persistence and modify the effects of climate change in the SWUS.